Can macroeconomic volatility affect stock market volatility? The case of 5 central and eastern European countries - Elena Baroian (Romanian Journal of Fiscal Policy (RJFP), 2014)
This paper examines whether macroeconomic instability can influence stock market volatility in a sample of 5 emerging European countries. To account for the effects of fundamentals, modified ARCH/GARCH models are employed. The results are discordant from one country to another, but when a dynamic panel GMM is estimated, exchange rate volatility is found to be the sole significant explanatory variable.
Keywords: C58; E44; G15; 330; Macroeconomic volatility; stock market volatility; panel estimation